Axiological Analysis of the Conceptual Categorial Apparatus of Professional Burnout in the System of Education - Ridei, Nataliia; Katsero, Oksana; Khitrenko, Tetiana; Daineko, Olena (Journal of Education, Technology and Computer Science, 2019)
The importance of professional health is actualized. The structural-logical scheme of the genesis of the conceptual-categorical apparatus of the study was constructed and its axiological and structural-functional analysis of “professional burnout” was carried out. Specifies the author’s interpretation of the definition of “professional burnout”; the structural and logical scheme of the process of professional burnout is developed.